2020
DOI: 10.1002/ange.202002951
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Morphology and Fractal Dimension of 2D Mesh‐like Gold Gels

Abstract: As there is a great demand of 2D metal networks, especially out of gold for a plethora of applications we show a universal synthetic method via phase boundary gelation which allows the fabrication of networks displaying areas of up to 2 cm2. They are transferred to many different substrates: glass, glassy carbon, silicon, or polymers such as PDMS. In addition to the standardly used web thickness, the networks are parametrized by their fractal dimension. By variation of experimental conditions, we produced web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Moreover, the gelation time and the yield, as two important factors for evaluating fabrication methods, were frequently overlooked or inappropriately used. Instead of lightly claiming minutes-or even seconds-level fabrication, 51,52 the comparison needs to be made under similar conditions (e.g., the amount of reactants, temperature, and the reactant concentrations). Moreover, only a handful of studies reported the yield.…”
Section: Toward Metal Aerogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the gelation time and the yield, as two important factors for evaluating fabrication methods, were frequently overlooked or inappropriately used. Instead of lightly claiming minutes-or even seconds-level fabrication, 51,52 the comparison needs to be made under similar conditions (e.g., the amount of reactants, temperature, and the reactant concentrations). Moreover, only a handful of studies reported the yield.…”
Section: Toward Metal Aerogelsmentioning
confidence: 99%
“…113,114 Recently, this phenomenon was also observed by using ethanol or ethanol/toluene, whereby 2D Au networks were obtained. 52 However, the underlying mechanism is unclear, and no self-supported aerogels were demonstrated. So far, the solvent has been applied as solvation agent, initiator, and morphology controller, while studies are rare and superficial.…”
Section: Self Assembly Dryingmentioning
confidence: 99%
“…Our fabrication scheme to obtain NPMFs can also be used to form transparent electrodes. An advantage to our method is that it can be used for large-scale fabrication and that our NPMFs show very low surface roughness, both are more challenging to address with other current schemes to obtain metal-based transparent electrodes. , The performance of transmittance and sheet resistance in our films is slightly lower than other metal-based transparent electrodes; , however, we believe that this can be improved by further optimizing fabrication parameters and that the ease of fabrication of large, smooth films is significant. We expect that our dry synthesis method, which is robust and can reproducibly yield impurity-free films, will open up new opportunities in the application of NPMs.…”
Section: Discussionmentioning
confidence: 98%
“…The nanoscale pore architecture directly determines the optical, electrical, chemical, and mechanical properties. The high surface-area-to-volume ratios and large number density of high surface energy atoms at curved surfaces give rise to significant catalytic activities that are absent in the bulk metal. , NPMs are also lightweight and can be optically transparent when they are very thin. , The interconnected films of NPMs have thus attracted strong interest for applications as electrode materials for synthesis, energy conversion, sensing, or as plasmonic materials . Since NPMs do not occur naturally, they need to be synthesized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation